A Case of Two Discourses: The Representation of the Canadian Cultural Divide in English and French Subject Headings - Desrochers, Nadine (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
The discursive space of the Canadian bilingual cataloguing system is examined for its representation of the people who inhabit the cultural places of Canada and, specifically, Québec. The intellectual construct of Québec as a distinct society is measured against the discourse of the two organizations responsible for the CSH and RVM. L’espace discursif du système de catalogage bilingue canadien est étudié pour sa représentation des gens qui habitent les espaces culturels du Canada et, spécifiquement, du Québec. Le concept intellectuel de société distincte est mesuré aux discours des deux organismes responsables, respectivement, des CSH et du RVM.